The Effect of Differences in The Use of EM4 Doses in The Fermentation of Teak Leaves (Tectona grandis) with The Addition of Molasses on Nutrient Content - Aris Nur Wahab; Catur Suci Purwati (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Teak leaves are an abundant waste product, but their use as animal feed is still limited due to their high fiber content and relatively low crude protein content. Their nutritional quality can be improved through a fermentation process. This study aimed to determine the effect of various doses of EM-4 (Effective Microorganism 4) on teak leaf fermentation to obtain the most optimal nutritional content. In this study, the design used was a Completely Randomized Design (CRD) with 4 treatments and 3 replications resulting in 12 treatment combinations. Each of which was divided into treatments P0 (0 ml), P1 (6 ml), P2 (12 ml), P3 (18 ml) and fermented for 14 days. Data were analyzed using analysis of variance (ANOVA), followed by Duncan's Multiple Range Test at a significance level of 5%. The results of the Duncan test showed that with different doses of EM - 4, there was no significant effect on crude fiber, dry matter, and crude protein (P>0.05). Although descriptively, there was an increase in crude fiber and crude protein content, and a decrease in dry matter content with increasing EM4 dosage, these changes were not statistically significant. In conclusion, differences in EM-4 dosage during fermentation did not significantly affect the nutritional content of crude fiber, crude protein, and dry matter.